Expanding the ‘American’ and Latina/o Theatre History Canons: The Case of Josefina Niggli - Noriega, Jimmy A. (Latin American Theatre Review, 2017)
This essay focuses on Josefina Niggli as an example by which to expand the American and Latina/o theatre history canons. In doing so, the article seeks to (re)interrogate and disrupt the ways that we construct and disseminate theatre history in our scholarship and teaching. Niggli provides a valuable lesson from which to reevaluate the roles of historiography and identity politics in the construction of our theatrical past precisely because her life and work are the products of two revolutions: the Mexican Revolution of 1910 and the US Little Theatre movement. Both are integral to understanding her biography and body of work, yet no study has merged the two in an effort to understand the ways each contributed to her place in theatre history. This essay presents highlights from Niggli’s biography as they relate to the larger Little Theatre movement and concludes with an analysis of her play Soldadera.